Oxidative stress caused by blocking of mitochondrial complex I H(+) pumping as a link in aging/disease vicious cycle - Dlasková, Andrea; Hlavatá, Lydie; Jezek, Petr (The international journal of biochemistry & cell biology, 2008)
Vulnerability of mitochondrial Complex I to oxidative stress determines an organism's lifespan, pace of aging, susceptibility to numerous diseases originating from oxidative stress and certain mitopathies. The mechanisms involved, however, are largely unknown. We used confocal microscopy and fluorescent probe MitoSOX to monitor superoxide production due to retarded forward electron transport in HEPG2 cell mitochondrial Complex I in situ. Matrix-released superoxide production, the un-dismuted surplus (J(m)) was low in glucose-cultivated cells, where an uncoupler (FCCP) reduced it to half. Rotenone caused a 5-fold J(m) increase (AC(50) 2 microM), which was attenuated by uncoupling, membrane potential (DeltaPsi(m)), and DeltapH-collapse, since addition of FCCP (IC(50) 55 nM), valinomycin, and nigericin prevented this increase. J(m) doubled after cultivation with galactose/glutamine (i.e. at obligatory oxidative phosphorylation). A hydrophobic amiloride that acts on the ND5 subunit and inhibits Complex I H(+) pumping enhanced J(m) and even countered the FCCP effect (AC(50) 0.3 microM). Consequently, we have revealed a new principle predicting that Complex I produces maximum superoxide only when both electron transport and H(+) pumping are retarded. H(+) pumping may be attenuated by high protonmotive force or inhibited by oxidative stress-related mutations of ND5 (ND2, ND4) subunit. We predict that in a vicious cycle, when oxidative stress leads to higher fraction of, e.g. mutated ND5 subunits, it will be accelerated more and more. Thus, inhibition of Complex I H(+) pumping, which leads to oxidative stress, appears to be a missing link in the theory of mitochondrial aging and in the etiology of diseases related to oxidative stress.
Keywords: mitochondriální DNA; respirační komplex I; oxidační stres; DNA, Mitochondrial; Mitochondria; Glucose; Fluorescent Dyes; Uncoupling Agents; Aging; mutace; Superoxides; superoxidy; Cell Line, Tumor; konfokální mikroskopie; fosforylace; Disease; Membrane Potential, Mitochondrial; Phosphorylation; transport elektronů; glukosa; Microscopy, Confocal; Electron Transport; Rotenone; Intracellular Space; rozpřahující látky; lidé; rotenon; Humans; stárnutí; fluorescenční barviva; Electron Transport Complex I; membránový potenciál mitochondrií; nemoc; Mutation; nádorové buněčné linie; Oxidative Stress; intracelulární prostor; mitochondrie